Ethics, Public Policy, and Human Fetal Tissue Transplantation Research - Childress, James F. (Kennedy Institute of Ethics journal, 1991)
This article focuses on the deliberations of the National Institutes of Health Human Fetal Tissue Transplantation Research Panel in 1988. It explores various arguments for and against the use of fetal tissue for transplantation research, following elective abortion, and for and against the use of federal funds for such research. After examining the relevance of various positions on the moral status of the fetus and the morality of abortion, the article critically examines charges that such research, especially with federal funds, would involve complicity in the moral evil of abortion, would legitimate abortion practices, and would provide incentives for abortions. Finally, it considers whether the donation model is appropriate for the transfer of human fetal tissue and whether the woman who chooses to have an abortion is the appropriate donor of the tissue.